2007
DOI: 10.1016/j.matbio.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Control of matrix metalloproteinase catalytic activity

Abstract: SummaryAs their name implies, MMPs were first described as proteases that degrade extracellular matrix proteins, such as collagens, elastin, proteoglycans, and laminins. However, studies of MMP function in vivo have revealed that these proteinases act on a variety of extracellular protein substrates, often to activate latent forms of effector proteins, such as antimicrobial peptides and cytokines, or to alter protein function, such as shedding of cell-surface proteins. Because their substrates are diverse, MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
474
0
43

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(545 citation statements)
references
References 102 publications
(98 reference statements)
7
474
0
43
Order By: Relevance
“…MMP modulation is also closely linked to bone remodeling (39,40). In this regard, a study using a canine model of experimental OA showed that during the disease, some members of the MMP family are selectively located at the active subchondral bone resorption zone (19).…”
Section: Discussionmentioning
confidence: 99%
“…MMP modulation is also closely linked to bone remodeling (39,40). In this regard, a study using a canine model of experimental OA showed that during the disease, some members of the MMP family are selectively located at the active subchondral bone resorption zone (19).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, treatment of B16F10 cells with S100A8/S100A9 also stimulated the expression of furin (Fig. 6, A and B), a pro-protein convertase that regulates the enzymatic activity of some MMPs such as MMP-14 (MT1-MMP) (44). Thus, it is likely that furin activated MMP-14, which in turn activated MMP-2.…”
Section: Elevated Levels Of Metastasis In the Lungs Of Mice Lacking Umentioning
confidence: 91%
“…Thus, it is likely that furin activated MMP-14, which in turn activated MMP-2. This notion is supported by the demonstration that heterodimerization of activated MMP-14 with MMP-2 activates MMP-2 (44). The mechanism of activation of MMP-9 remains unclear.…”
Section: Elevated Levels Of Metastasis In the Lungs Of Mice Lacking Umentioning
confidence: 95%
“…10 The glutamate residue at the zinc binding motif activates the zinc-bound water molecule to provide the nucleophile during cleaving activities on peptide bonds. 11 A mutation in the zinc-binding motif from glutamate (E) to alanine (A) causes a loss of MMP19 function in cell proliferation, migration, and protein degradation in a human keratinocyte cell model. 12 MMP19 was first isolated as an autoantigen from the synovium of a rheumatoid arthritis patient.…”
mentioning
confidence: 99%